2020
DOI: 10.1293/tox.2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

Dog-specific hemorrhagic changes induced by liposomal formulations, in the liver and the gallbladder

Abstract: Although several liposomal drugs, including liposomal doxorubicin, have been approved, the etiology of the pathological responses caused by their physicochemical properties remains unknown. Herein, we investigated the pathological changes in the liver and the gallbladder of dogs following a single injection of liposomal doxorubicin (1 or 2.5 mg/kg) or an empty liposomal formulation (i.e., liposomal formulation without doxorubicin, ca. 21 mg/kg as lipid content). Injection of liposomal doxorubicin or the empty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…More recent work has indicated a sensitivity for dogs from intravenous dosing of the doxorubicin-free liposomal formulation of Doxil ® (empty liposome). 39 Macroscopical observations of reddish foci in liver and gall bladder correlated to histopathological changes of perivascular hemorrhage and dilated lymphatic vessels in liver and hemorrhage in gall bladder. Decreased cytoplasmic granules in mast cells beneath endothelium of hepatic vein were noted.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…More recent work has indicated a sensitivity for dogs from intravenous dosing of the doxorubicin-free liposomal formulation of Doxil ® (empty liposome). 39 Macroscopical observations of reddish foci in liver and gall bladder correlated to histopathological changes of perivascular hemorrhage and dilated lymphatic vessels in liver and hemorrhage in gall bladder. Decreased cytoplasmic granules in mast cells beneath endothelium of hepatic vein were noted.…”
Section: Resultsmentioning
confidence: 96%
“…These effects were considered to be related to reactions to the physicochemical properties of liposomes such as their particle size, surface charges, PEG and cholesterol ratio. 39,40 Investigation has shown that the complement system is activated by phospholipid bilayers after liposomal injections, which leads to complement production, mediated by anaphylatoxins, and subsequent release of histamine from mast cells; this phenomenon has been named C activation-related pseudoallergy (CARPA). 41 In addition, for PEGylated liposomes, work with Caelyx TM /Doxil ® using plasma from mice and human volunteers has demonstrated that anti-PEG antibodies may contribute to complement activation.…”
Section: Resultsmentioning
confidence: 99%